2005
DOI: 10.1111/j.1462-5822.2005.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium ulcerans toxic macrolide, mycolactone modulates the host immune response and cellular location of M. ulcerans in vitro and in vivo

Abstract: SummaryMycobacterium ulcerans produces an extracellular cutaneous infection (Buruli ulcer) characterized by immunosuppression. This is in stark contrast to all other pathogenic Mycobacteria species that cause intracellular, granulomatous infections. The unique mycobacterial pathology of M. ulcerans infection is attributed to a plasmid-encoded immunomodulatory macrolide toxin, mycolactone. In this article we explore the role of mycolactone in the virulence of M. ulcerans using mycolactone and genetically define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
140
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(148 citation statements)
references
References 39 publications
4
140
0
3
Order By: Relevance
“…In the ulcerative non-granulomatous lesions it was common that bacteria were overlying cells, but in some peripheral areas distant to necrosis we found fewer and dispersed bacilli; in these areas some macrophages showed well-defined intracellular AFB, suggesting real phagocytosed mycobacteria. This observation is in agreement with recent in vitro studies which demonstrated that occasional macrophages can be infected by M. ulcerans [23], and with the concept that M. ulcerans has an intracellular phase that is necessary for the induction of a Th1 immune response [24,25]. It has been demonstrated recently that mycolactone is anti-phagocytic, but macrophages can phagocytose M. ulcerans during early experimental infection and transport the bacilli to the regional lymph nodes [26].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the ulcerative non-granulomatous lesions it was common that bacteria were overlying cells, but in some peripheral areas distant to necrosis we found fewer and dispersed bacilli; in these areas some macrophages showed well-defined intracellular AFB, suggesting real phagocytosed mycobacteria. This observation is in agreement with recent in vitro studies which demonstrated that occasional macrophages can be infected by M. ulcerans [23], and with the concept that M. ulcerans has an intracellular phase that is necessary for the induction of a Th1 immune response [24,25]. It has been demonstrated recently that mycolactone is anti-phagocytic, but macrophages can phagocytose M. ulcerans during early experimental infection and transport the bacilli to the regional lymph nodes [26].…”
Section: Discussionsupporting
confidence: 80%
“…It has been demonstrated recently that mycolactone is anti-phagocytic, but macrophages can phagocytose M. ulcerans during early experimental infection and transport the bacilli to the regional lymph nodes [26]. Mutant M. ulcerans unable to produce mycolactone is phagocytosed easily by macrophages and induced well-formed granulomas in experimental animal models [23,25,26]. Thus, the few bacilli that we detected in the cytoplasm of macrophages could correspond to dead bacilli or to bacteria which lacked toxin production, facilitating their phagocytosis.…”
Section: Discussionmentioning
confidence: 76%
“…It should be noted that some natural macroliderelated molecules act as toxins, such as mycolactones, which are 12C-membered macrolide lactones. These molecules are produced by different members of the genus Mycobacterium, including Mycobacterium marinum, Mycobacterium pseudoshottsii, Mycobacterium liflandii (Hong et al, 2008;Kishi, 2011;Mve-Obiang et al, 2005;Ranger et al, 2006) or Mycobacterium ulcerans, the most relevant at human clinical level due to the production of a series of mycolactones considered to be responsible for the unique characteristics of Buruli ulcer (Adusumilli et al, 2005). At present, at least nine different M. ulcerans mycolactones have currently been described.…”
Section: Structure and Classificationmentioning
confidence: 99%
“…Mycolactone inhibits the production of various cytokines, chemokines, and other secreted immune modulators [7] from immune cells such as monocytes [8], macrophages [9], dendritic cells [10], and T cells [11][12][13]. When a mycolactone-deficient strain of M. ulcerans was injected into model animals, a granuloma was successfully developed and the bacteria were cleared from the infected regions [14,15], suggesting that mycolactone has a suppressive effect on cell-mediated immune responses. However, the effects of mycolactone on serum immune responses remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%